The effect of p-tolyl-sulfonylamido units on thermal stability, mesogenic, photophysical properties and base sensitivity of unsymmetrical Zn(II) phthalocyanines - Pur, Bilge; Yüksel, Fatma; Ahsen, Vefa (Elsevier Sci Ltd, 2012)
Two unsymmetrically substituted phthalocyanines bearing six alkoxy moieties (3a) and six alkoxy facing two p-tolyl-sulfonyl(tosyl)amido moieties (3b) were synthesized by cyclotetramerization reactions of corresponding two different phthalonitrile derivatives in the presence of an anhydrous Zn(AcO)(2) and strong base. These novel compounds were fully characterized by elemental analyses, IR, H-1 and C-13 NMR and Mass spectra. The thermal stabilities of the phthalocyanine compounds were determined by thermogravimetric analysis (TGA). The mesogenic properties of these new materials were studied by differential scanning calorimeter (DSC) and optical microscopy. Absorption and emission based spectral characterization were done in THF. The base sensitivity of both compounds was examined with absorbance and fluorescence spectrophotometer in THF. The effect of tosylamido units on thermal stability, and mesogenic, photophysical and base sensitivity properties were discussed by comparing two compounds. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Asymmetrical phthalocyanine; Liquid crystal; Metallomesogen; Discotic; Fluorescence; pH sensitivity